The under-representation of minority ethnic groups in UK medical research. Issue 1 (2nd January 2017) - Smart, Andrew; Harrison, Eric
ABSTRACT: Objectives . The paper investigates differences in engagement with medical research between White British and Black, Asian and Minority Ethnic (BAME) groups in the UK, using data from the Wellcome Trust Monitor (WTM). Design. The study used two waves of the WTM ( n = 2575) to examine associations between ethnic group and participation in medical research, and willingness to participate (WP) in medical research. Logistic regression models controlled for socio-economic and demographic factors, and relevant outlooks and experiences that are assumed to be markers of engagement. Results. Respondents from the BAME group were less likely to have participated in medical research compared to those from the White British group, but there was only patchy evidence of small ethnic group differences in WP. Influences on engagement with medical research varied somewhat between the White British and BAME groups, in particular in relation to occupation, education, health, attitudes to medical science and belief. Conclusions. These findings consolidate previously context-specific evidence of BAME group under-representation in the UK, and highlight heterogeneity in that group. Efforts to address the under-representation of those from BAME groups might benefit from targeted strategies for recruitment and advocacy, although improved data sets are required to fully understand ethnic differences in engagement with medical research.